Oral Diseases Panorama in Dermatology: An Observational Study - Khan, Mohd Rizwan (International Journal of Innovative Research in Medical Science, 2020)
Background: The oral cavity is a mirror of the body, entry point to food, antigens, and microorganisms. Oral cavity with mastication and speech, also have a role play in immunological defense. The Oral mucous membrane is in link with skin, oropharynx, and nasopharynx. The oral cavity and anterior two-thirds of the tongue are formed by the ectoderm and that is why from a dermatologist's viewpoint, an oral opening is especially imperative and involved in a range of systemic and skin disease, also affect teeth and gums. The body's natural protection is in good quality oral care. Oral problems when associated with skin conditions require oral care as it affects the quality of life and enable dermatologist and dentist in the identification and diagnosing of systemic disease. Oral illness can bring into being from infection, inflammation or neoplastic, immunological, benign, or malignant. Results: The oral cavity is a mirror to a variety of systemic and cutaneous diseases. Interpretation of the symptom and signs of systemic diseases help early diagnosis. However, while not correct oral hygiene, microorganisms will reach levels that may result in oral infections and decay. The health status of our oral cavity can give us a strong signal of the health of our bodies. It proceeds as a premature warning system. That's why the oral cavity should be examined in one piece from the buccal mucosa to the oropharynx. Conclusion: The mouth is a straightforwardly available window of the body. In contemplation with development, composition, and utility oral cavity is only one of its kind. It is a two-way road as systemic skin disease has oral manifestation. Interpretation of the symptom and signs help in identification and early diagnosis of systemic diseases. Oral illness can bring into being from infection, inflammation or neoplastic, immunological, benign, or malignant. That's why the oral cavity should be examined in one piece from buccal mucosa, lips, tongue, gum, teeth, palate to the oropharynx. Knowledge of systemic diseases is vital in day to day clinical practice, often oral manifestation is the most significant or first sign of systemic illness. So dermatologists and dental surgeons are conscious of oral complaints and their association with systemic disease.